Development of Better Teaching and Learning Models in the Competence of Basic Teaching Skills of Students - Siti Wahida; Marnala Tobing; Dina Ampera; Astrid Sitompul; Yudhistira Anggraini (Universitas Muhammadiyah Yogyakarta, 2022)
The objectives of this study are: (1) to develop a Better Teaching and Learning model that can foster character, increase student interest, activity, and learning outcomes in teaching exercises, and determine the validity, effectiveness, and practicality of the Better Teaching and Learning model. This research is a research development (RD). The research was carried out in three stages: (1) Theoretical exploration and expert research on the Better Teaching and Learning model. (2) Empirical test to empirically validate the Better Teaching and Learning model. (3) The implementation stage to determine the effectiveness and practicality of the Better Teaching and Learning model. The results showed that the Better Teaching and Learning model was developed to integrate the basic teaching skills and was presented in eight stages of teaching skills. This model is declared valid by the validator and supported by empirically validated results through field trials. This model has also been tested for its effectiveness in fostering character and increasing student interest, activity, and cognitive learning outcomes. The practice of implementing the Better Teaching and Learning model has also been tested through observations of the ability of prospective teachers in classroom learning, learning responses to the ease with which prospective teachers use the Better Teaching and Learning model, and student acceptance responses to the Better Teaching and Learning model applied by a pre-service teacher. The final result shows that the Better Teaching and learning model developed has met the criteria of validity, effectiveness, and practice.